BOBOT BADAN BERBAGAI AYAM KEDU UMUR 5 DAN 8 BULAN DI KELOMPOK TERNAK MAKUKUHAN MANDIRI KECAMATAN KEDU KABUPATEN TEMANGGUNG - Azizah, Hanan Fathinah Nur; Rosidi, Rosidi; Suswoyo, Imam (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Backgrund. This research aims to measure body weight of various Kedu Chickens at 5 and 8 weekss age. Materials and Methods. The variesty of breeds of Kedu chickens was based on feather colors i.e. cemani, Black, White, Red, and Lurik. Sampling was done using purposive sampling. General Linear Model was applied and followed by Tukey. Results. The average of Male Kedu chicken body weight at 5 weeks of age was 799,82 ± 15,85 g and or female it was 1408,44 ± 30,15 g. While the average of Male Kedu chicken body weight at 8 weeks age was 2481,20 ± 61,77 g; and 1744,79 ± 48,16 g for female. The result of Variance analysis showed that there was a significant different (P<0,05) among kedu chicken body weight in 5 age of weeks, but no significant (P>0,05) at 8 weeks of age. Simpulan. The conclusion Male Cemani Body weight in 5 weeks of age had lower body weight than Black Kedu and relatively equal with other breeds.All breeds of Female Kedu Chicken at 5 and 8 weeks of age had relatively similar body weight.